Oídio (Sphaerotheca pannosa) y su incidencia en el cultivo de rosas de exportación en el Ecuador - Sig Tu Acosta, Luis Bernabe (2024)
Powdery mildew, caused by the fungus Sphaerotheca pannosa var. rosae, poses a serious threat to rose production and export in Ecuador and globally. This disease affects the quality of roses by reducing production and weakening plants, resulting in significant economic losses for producers. Despite the widespread use of agrochemicals as the primary method for control, this practice presents challenges in terms of sustainability and environmental risks. In this context, this research focuses on identifying integrated strategies for powdery mildew control in export rose cultivation in Ecuador. A detailed study was conducted on the edaphoclimatic characteristics that favor disease development, as well as integrated powdery mildew management, which includes appropriate cultural practices, rational use of fungicides, and biological control agents. The findings revealed that powdery mildew significantly affects export rose cultivation in Ecuador, impacting both the quality and production of flowers. However, various control measures were identified that can be implemented sustainably, such as integrated powdery mildew management, which combines different control methods to reduce disease incidence and severity. In conclusion, this research offers practical recommendations for Ecuadorian floricultural producers, emphasizing the importance of applying cultural control measures and using fungicides appropriately to minimize environmental impacts and ensure sustainable production of export roses.